Innovative Genius: A Framework for Relating Individual and Organizational Intelligences to Innovation - Glynn, Mary Ann (Academy of Management Review, 1996)
In this article, organizational innovation is viewed as fundamentally cognitive, and the concept of organizational intelligence is developed and related to innovation. Individual and organizational intelligences are conceptualized as being functionally similar (i.e., as purposeful information processing that enables adaptation to environmental demands). Organizational intelligence, however, is a social outcome and is related to individual intelligence by mechanisms of aggregation, cross-level transference, and distribution. A conceptual framework is proposed that relates types and levels of intelligence, moderated by contextual factors, to the two stages of the organizational innovation process: initiation and implementation. Implications for research and management are discussed.